RIP CURRENTS SIGNATURES ZONE DETECTION ON ALOS PALSAR IMAGE AT PARANGTRITIS BEACH, INDONESIA - Arry Retnowati; Muh Aris Marfai; J.T. Sri Sumantyo (Indonesian Journal of Geography, 2012)
Having bay and gulf morphology as cresentic beach, Parangtritis coast has been known potentiallythreat by rip currents hazard. This study aims to identify and detect breaking wavesregion and surf zone on ALOS PALSAR images, and identify and extract the cove shapeshoreline morphology of Parangtritis beach. ALOS PALSAR Fine Beam Single (FBS) HH polarizationacquired on 2nd May 2007 and 17th June 2007, off nadir angle 34.3º, and in descendingmode level 1.0 were utilized to derive amplitude information using Sigmasar. Shorelinemorphology detection showed that the cusps system has not changed much during May toJune 2007 when PALSAR images acquired, but might have shifted individually. The use ofoptical sensor with the same spatial resolution, ALOS AVNIR-2, supports to distinguish theboundary and determine the shoreline morphology of Parangtritis beach.